University foodservice: an overview of factors influencing the customers' dining choice - Salehuddin, Nadzirah; Abdul Karim, Muhammad Shahrim; Ghazali, Hazrina; Othman, Mohhidin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
On-campus foodservices were thought to be the first choice for university students to dine in. However, these seemingly captive consumers have been opting for off-campus foodservice as their preferred outlet. This paper aims to uncover specific factors that motivate undergraduate students to dine-in at university foodservice facilities using Profile Accumulation Technique (PAT). PAT is a semi-quantitative method that provides freedom for informants to answer in their own terms and words, alternatively the data could be analyzed statistically. 115 questionnaires were distributed to students and staff of a local university. Findings include a list of factors (positive perception, negative perception and expectations) that the students considered to be significant in determining their choice of food outlet. These factors are then descriptively analyzed to determine attributes influencing university customer preferences. This paper significantly contributes in providing a deeper insight into factors that influences dining choice of university foodservice’s customers in Malaysia.